Act like a leader, think like a leader - Ibarra, Herminia, 1961- (Ascent Audio, 2023)
You aspire to lead with greater impact. The problem is you're busy executing on today's demands. You know you have to carve out time from your day job to build your leadership skills, but it's easy to let immediate problems and old mindsets get in the way. Leadership and development expert Herminia Ibarra shows how managers and executives at all levels can step up to leadership by making small but crucial changes in their jobs, their networks, and themselves. In Act Like a Leader, Think Like a Leader, she offers advice to help you redefine your job in order to make more strategic contributions; diversify your network so that you connect to, and learn from, a bigger range of stakeholders; and become more playful with your self-concept, allowing your familiar-and possibly outdated-leadership style to evolve. Ibarra turns the usual "think first and then act" philosophy on its head by arguing that doing these three things will help you learn through action and will increase what she calls your outsight-the valuable external perspective you gain from direct experiences and experimentation. As opposed to insight, outsight will then help change the way you think as a leader: about what kind of work is important; how you should invest your time; why relationships matter in informing and supporting your leadership; and, ultimately, who you want to become.